"Whatever It Takes!" How Tonality of TV-News Affected Government Bond Yield Spreads during the European Debt Crisis - Patrick Hirsch; Lars P. Feld; Ekkehard A. Köhler; Tobias Thomas (Center for Economic Studies and ifo Institute (CESifo), 2024)
Were government bond risk premia affected by the media in addition to the effects of major events? Revisiting the European debt crisis, we analyze the role of television news in the rise and re-convergence of GIIPS bond spreads vis-à-vis Germany from 2007 to 2016. We use a dataset of more than one million human-coded news items from leading newscasts worldwide to identify over 25,000 news on the Eurozone and country-specific economic topics. Our findings emphasize the relevance of the tonality of news, such that an increasing share of positive (negative) news correlates with a decrease (increase) in spreads. Content-based endogenous clustering of news highlights the importance of news about institutions providing stability and "international financial support" to distressed countries in reducing bond spreads. Moreover, weekend news enables us to establish a causal link between country-specific news coverage and changes in spreads on the subsequent trading day.
Keywords: E58; G12; L82; 330; media coverage; TV newscast; tonality; Eurozone crisis; GIIPS bond yield spreads